Experimental Test on Server Power Consumption Based on Performance Testing Software - Xu Xin; Bai Xuelian; Jin Chaoqiang (Zhileng xuebao)
Determining the power consumption of data center servers is the basis of data center energy saving and environmental control. At present, it is a common research method that uses performance testing software to fit the server power consumption model under different working conditions. An experimental platform was built with the aim of CPU computing as the main task. Three different test software (Lookbusy, Stress, and SPECpower_ssj 2008) were used to conduct the test. This study compared the differences between server power consumption and hardware utilization based on server operating parameters. The results show apparent differences in server hardware calls under an identical parameter setting among different testing software, leading to a maximum deviation of more than 15% on the testing outcome of the server power consumption. This indicates that it is important to select the proper performance testing software according to application scenarios and hardware utilization when it comes to the research of the server power consumption model. Among the software tested, SPECpower_ssj 2008 is most suitable for the comprehensive testing of servers, and Stress is most suitable for testing the stability of servers under extreme conditions.